Triimide‐Functionalized n‐Type Polymer Semiconductors Enabling All‐Polymer Solar Cells with Power Conversion Efficiencies Approaching 9%. Issue 7 (10th May 2019) - Wang, Yingfeng; Yan, Zhenglong; Uddin, Mohammad Afsar; Zhou, Xin; Yang, Kun; Tang, Yumin; Liu, Bin; Shi, Yongqiang; Sun, Huiliang; Deng, Aiying; Dai, Junfeng; Woo, Han Young; et al.
Abstract : Two triimide‐functionalized n‐type acceptor polymers are designed and synthesized, which show narrower bandgap, lower‐lying frontier molecular orbital energy levels, and improved film morphology than the diimide‐functionalized analogue polymers. When blended with a p‐type donor polymer semiconductor PTB7‐Th, an outstanding power conversion efficiency of 8.98% with a remarkable open‐circuit voltage of 1.03 V is attained. This efficiency is among the highest values in all‐polymer solar cells (all‐PSCs) reported till today, surpassing that (6.85%) of the diimide‐functionalized analogue polymers by a big margin and even higher than that (8.69%) of the fullerene‐based solar cells. The results demonstrate that the triimide‐functionalized f‐BTI3 is an excellent building block for developing n‐type polymer semiconductors, and the polymer f‐BTI3‐T is among the best‐performing n‐type polymers for applications in all‐PSCs. The structure–property correlations of these imide‐functionalized polymer semiconductors offer important guides for developing high‐performance n‐type polymer semiconductors. Abstract : Triimide‐functionalized n‐type polymers are synthesized and used as the acceptor materials in all‐polymer solar cells (all‐PSCs), and a remarkable power conversion efficiency of 8.98% is achieved, which is among the highest values in all‐PSCs. The results demonstrate the positive effects of increasing imide number in polymer acceptors on improving all‐polymer solar cell performance.